2020
DOI: 10.1111/iep.12377
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐590‐3p regulates cardiomyocyte P19CL6 proliferation, apoptosis and differentiation in vitro by targeting PTPN1 via JNK/STAT/NF‐kB pathway

Abstract: Cardiomyocyte differentiation is a multi-step process which involves a number of signalling pathways. microRNAs exhibit regulatory functions in various diseases and are involved in the signalling pathways in multiple physiological processes, but the specific functions of particular mRNAs is often not fully understood. of an example of this is that the role of miR-590-3p in the differentiation of cardiomyocytes remains unclear. In the current study, RT-qPCR was used to determine the expression of miR-590-3p in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…miR‐590‐3p is known to regulate the proliferation, apoptosis by targeting PTPN1 via the JNK/STAT/NF‐kB pathway. 55 , 56 miR‐106a and let‐7 are also known to regulate the NF‐kB pathway, 57 , 58 confirming the previous observations in several cancer cell lines that curcumin exerts its effect via the inhibition of the NF‐kB pathway. To dissect the mechanism of NF‐KB inhibition induced by curcumin treatment, we further analyzed the NF‐kB pathway in all three cells upon curcumin treatment.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…miR‐590‐3p is known to regulate the proliferation, apoptosis by targeting PTPN1 via the JNK/STAT/NF‐kB pathway. 55 , 56 miR‐106a and let‐7 are also known to regulate the NF‐kB pathway, 57 , 58 confirming the previous observations in several cancer cell lines that curcumin exerts its effect via the inhibition of the NF‐kB pathway. To dissect the mechanism of NF‐KB inhibition induced by curcumin treatment, we further analyzed the NF‐kB pathway in all three cells upon curcumin treatment.…”
Section: Resultssupporting
confidence: 77%
“…In MCF7 miR‐590‐3p, in MDA‐MB‐231 miR‐106a‐3p and in T47D let‐7c‐3p regulates maximum number of DE genes upon curcumin treatment. miR‐590‐3p is known to regulate the proliferation, apoptosis by targeting PTPN1 via the JNK/STAT/NF‐kB pathway 55,56 . miR‐106a and let‐7 are also known to regulate the NF‐kB pathway, 57,58 confirming the previous observations in several cancer cell lines that curcumin exerts its effect via the inhibition of the NF‐kB pathway.…”
Section: Resultssupporting
confidence: 72%
“…In the past reports, miR-590-3p was confirmed to participate in cancer progression as a tumor suppressor, including hepatocellular carcinoma (Pu et al, 2020), breast cancer (Shan et al, 2020), and papillary thyroid carcinoma (Tong et al, 2019). Wang et al showed that miR-590-3p silencing inhibited cardiomyocytes proliferation and differentiation, while it accelerated apoptosis (Wang F. et al, 2020). More importantly, miR-590-3p was found to restore cell cycle process to promote cardiomyocytes proliferation, and thus alleviating AMI progression (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…miR‐199 was shown to inhibit Cd151 and, in turn, up‐regulate the pro‐proliferative pathway previously inhibited by Cd151‐p38 axis 45 . Similarly, miR‐590 targets Protein Tyrosine Phosphatase Non‐Receptor Type 1 (PTPN1), which promotes proliferation of CM through JNK/STAT/NF‐kB axis 46 . On the other hand, studies identified the miRNA‐15 (miR‐15) family as a key antiproliferative player in cardiomyocyte cell cycle withdrawal 47 (Figure 2).…”
Section: Foetal Versus Adult CM Description Of Major Changes During M...mentioning
confidence: 99%
“…45 Similarly, miR-590 targets Protein Tyrosine Phosphatase Non-Receptor Type 1 (PTPN1), which promotes proliferation of CM through JNK/STAT/NF-kB axis. 46 On the other hand, studies identified the miRNA-15 (miR-15) family as a key antiproliferative player in cardiomyocyte cell cycle withdrawal 47 (Figure 2). Members of the miR-15 family (À15a, À15b, 16-a, À16b, À195, and À497) target genes related to the cell cycle (Chek1, Cdc2a, Birc5, Nusap1, and Spag5) and start to be expressed shortly after birth, reaching a peak around week 2 in mice, coinciding with the end of the transient proliferative window of CM after birth.…”
Section: Morphology and Cell Cyclementioning
confidence: 99%